Effect of admission blood glucose on early mortality in patients with pontine hemorrhage - Junqing Ma; Junhong Hao; Lan Xu; Xiaowei Miao; Yanquan Hou; Zujun Song (Scientific Reports)
Abstract Elevated admission blood glucose (ABG) is increasingly recognized as a prognostic marker in intracerebral hemorrhage, but its specific role in pontine hemorrhage (PH) remains underexplored. This retrospective study analyzed data from 247 PH patients admitted to two tertiary hospitals between 2012 and 2016 to evaluate the association between ABG and 30-day mortality. Receiver operating characteristic analysis identified 8.69 mmol/L as the optimal hyperglycemia threshold predictive of mortality. Survival analysis revealed significantly lower 30-day survival rates in hyperglycemic patients compared to non-hyperglycemic patients (P = 0.0017). In multivariate regression models, ABG (per 1 mmol/L increase) independently increased mortality risk, with an adjusted odds ratio (aOR) of 1.295 (P = 0.0097) in the overall cohort and an aOR of 1.266 (P = 0.0210) in the nondiabetic patients. Hyperglycemia was significantly associated with increased mortality compared to non-hyperglycemia, with an aOR of 3.641 (P = 0.0024) in the overall cohort and an aOR of 3.492 (P = 0.0035) in the nondiabetic subgroup. Notably, no significant association was observed in diabetic patients (P > 0.05). These findings suggest that elevated ABG serves as an independent predictor of 30-day mortality following PH, particularly in nondiabetic populations, and may facilitate early risk stratification.